DWIE SFERY OSOBOWOŚCI STUDENTA RUSYCYSTY - Janaszek, Krystyna (Przegląd Rusycystyczny, 2019)
TWO SPHERES OF PERSONALITY OF A RUSSIAN STUDIES STUDENT This paper presents the results of questionnaire survey conducted among 65 students of Russian studies at the University of Szczecin. The survey concerned the cognitive sphere of personality that takes into account the mental aptitude of respondents and the affective sphere associated with the plane of feelings and emotions that accompany the process of language learning. During the study, the factors which specifically characterise the examined sample of students were identified. In the cognitive sphere, they are as follows: intelligence (linguistic and interpersonal), mechanical visual and auditory memory, cognitive styles (field independence, reflexivity), approaches to linguistic phenomena (styles: logical, wide, open), and communication achievement strategies (the so-called increased risk strategies). The most important factors of the affective sphere are: extrovert-introvert personality type, instrumental and integrative motivation to learn a foreign language, law and undervalued assessment of own language skills. Most students showed the ability to cope with emotions and resistance to stress. ДВЕ СФЕРЫ ЛИЧНОСТИ СТУДЕНТА-РУСИСТА В статье представлены результаты исследований, проведённых среди 65 студентов-русистов Щецинского университета. Анкетные данные относятся к когнитивной сфере личности, предусматривающей интеллектуальные наклонности исследуемых, а также к аффективной сфере, определяющей спектр чувств и эмоций, связяанных с процессом языкового обучения. В ходе исследований были установлены факторы, которые отдельным способом характеризуют исследуемую выборку студентов. В когнитивной сфере выступают следующие факторы: интеллект (лингвистический и межличностный), механическая зрительная память, механическая слуховая память, познавательные стили (независимость от поля, рефлексивность), способы подхода к языковым явлениям (стили: логический, широкий, открытый), а также коммуникативные стратегии успехов (так называемые стратегии повышенного риска). К наиболее существенным элементам аффективной сферы относятся: экстравертно-интровертный тип личности, инструментально-интегрирующая мотивация, низкая и заниженная оценка собственных языковых знаний. Большинство студентов проявляет умение справляться с эмоциями и стрессом.